2021
DOI: 10.1021/acs.energyfuels.1c00936
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Particle Size of Porous Media on the Formation of Natural Gas Hydrate: A Review

Abstract: As a new source of energy with great potential, natural gas hydrate (NGH) will play an indispensable and important strategic role in the future because of its tremendous reserves and wide application prospects in industry. It is of great significance to study the factors affecting the formation and occurrence of NGH for its exploration and exploitation under natural conditions and its application in industry. Since the sediments where NGH are mostly found are in porous media, the impact of porous media on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 195 publications
0
20
0
Order By: Relevance
“…As a whole, the gas consumption rate in the water conversion range of 0–40% in 2.30 μm silicon dioxide powder is higher than that in 5.54 μm silicon dioxide powder. For the porous media with a smaller particle size, the pores in porous media are smaller and the specific surface area is larger, providing a larger contact area of gas and water and reaction interface. , Therefore, the hydrate formation rate is higher in the early stage in 2.30 μm silicon dioxide powder. When the water conversion is higher than 50%, the gas consumption in 2.30 μm silicon dioxide powder becomes lower than that in 5.54 μm silicon dioxide powder.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a whole, the gas consumption rate in the water conversion range of 0–40% in 2.30 μm silicon dioxide powder is higher than that in 5.54 μm silicon dioxide powder. For the porous media with a smaller particle size, the pores in porous media are smaller and the specific surface area is larger, providing a larger contact area of gas and water and reaction interface. , Therefore, the hydrate formation rate is higher in the early stage in 2.30 μm silicon dioxide powder. When the water conversion is higher than 50%, the gas consumption in 2.30 μm silicon dioxide powder becomes lower than that in 5.54 μm silicon dioxide powder.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure , it also can be found that the hydrate formation rate at 7 °C is higher than that at 3 and 5 °C, indicating that the hydrate formation in 229.90 μm silica sand has stronger randomness than those in 2.30 and 5.40 μm silicon powders. Qin et al analyzed that the water is less bound in the unsaturated bed with a larger sand particle size as a result of the smaller specific surface area. , Therefore, in 229.90 μm silica sand, a larger amount of water will accumulate at the bottom under the action of gravity, resulting in the uneven distribution of water in the bed and the randomness of the hydrate formation rate in the early stage. At the same time, it should be pointed out that the accumulation and uneven distribution of water caused by gravity should be more significant in the reactor with a larger inner volume, the randomness of the hydrate formation would be more notable, and the effect of water distribution on the hydrate formation rate should be taken into account.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural gas hydrate occurs in continental margin sediments [4,12,13,18]. The hydrate-bearing sediment has complex pore structures, unique interfacial properties, and various mineral compositions, prompting huge contrasts between the formation of gas hydrates in the confined space and that in the free space [19][20][21][22][23]. The formation process, structure, and distribution of natural gas hydrates in sediments have become focal points of exploring natural gas hydrates [24][25][26].…”
Section: Introductionmentioning
confidence: 99%